2020
DOI: 10.37605/pjhssr.3.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Predicting Role of Students Grit in Boosting Hope, Meaning in Life and Subjective Happiness Among Undergraduates of University

Abstract: The present research examines how the presence of students’ psychological grit can boost up hope, meaning in life, and subjective happiness of 475 undergraduate students. To test this model, students’ grit is used as predictor of presence of hope, meaning in life, and subjective happiness. Student’s grit influences the passion and perseverance of the undergraduate students of the university to achieve their short and long-term goals. We administered grit scale, hope scale, meaning in life scale and subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…In fact, other studies have reported a unidimensional structure for grit and/or used a total grit score compiled of PE and CI items (e.g., Areepattamannil & Khine, 2018; Baierschmidt, 2022; Cerda et al, 2018; Eskreis-Winkler et al, 2014; Gonzalez et al, 2020; He, Wang et al, 2021; Hossain et al, 2022; Ion et al 2017; Kannangara et al, 2018; Kooken et al, 2021; Lee & Sohn, 2017; Luthans et al, 2019; Muhammad et al, 2020; Sinclair, 2021; Usher et al, 2019). However, further studies have shown that grit is composed of two correlated factors.…”
Section: The Concept Of Gritmentioning
confidence: 99%
“…In fact, other studies have reported a unidimensional structure for grit and/or used a total grit score compiled of PE and CI items (e.g., Areepattamannil & Khine, 2018; Baierschmidt, 2022; Cerda et al, 2018; Eskreis-Winkler et al, 2014; Gonzalez et al, 2020; He, Wang et al, 2021; Hossain et al, 2022; Ion et al 2017; Kannangara et al, 2018; Kooken et al, 2021; Lee & Sohn, 2017; Luthans et al, 2019; Muhammad et al, 2020; Sinclair, 2021; Usher et al, 2019). However, further studies have shown that grit is composed of two correlated factors.…”
Section: The Concept Of Gritmentioning
confidence: 99%
“…Studi ini selain membuktikan bahwa harapan berpengaruh signifikan terhadap Grit juga mampu membuktikan bahwa pengaruhnya bersifat moderat (18%). Selain itu, penelitian oleh Muhammad et al, (2020) dan Lee, et al, (2022) juga menunjukkan bahwa harapan merupakan prediktor terkuat Grit dengan R 2 sebesar 0,32 dan 0,33. Sejauh ini, dua penelitian tersebut menunjukkan hasil paling mirip dengan studi ini.…”
Section: Pembahasanunclassified
“…Studies between Grit and work happiness have provided results and implications for situational adaptability and growth within the workplace ( Datu et al, 2017 ). Grit and job happiness were shown to be predictors of other psychological constructs such as hope, meaning in life, and subjective well-being ( Muhammad et al, 2020 ). Similarly, it was shown that people who are more goal-oriented tend to be happy and satisfied with their lives, as they use persistence, consistency, and well-being as a foundation for career success ( Mazhar Khan and Khan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%